2007
DOI: 10.1080/09593332808618762
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Mining Wastes on the Physicochemical and Biological Characteristics of Groundwater in a Mining Area in Marrakech (Morocco)

Abstract: Metal sulphide tailings represent a potential risk basically for the environment and particularly for water resources, because of their natural oxidisability which leads to the production of acid/neutral mine drainage. The prospected site close to Marrakech includes zinc, lead and copper sulphide deposits. This site is located in an agricultural area where ground water is used both for irrigation and drinking. Eco-toxicological investigations have been undertaken in order to asses the tailings impact on water … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
2
0
2

Year Published

2008
2008
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(5 citation statements)
references
References 0 publications
1
2
0
2
Order By: Relevance
“…This relationship between water quality and richness of stygofauna has already been shown in the case of organic (Ait Boughrous et al, 2007) or inorganic e.g. (El Adnani et al, 2006;El Adnani et al, 2007) pollution. These studies have frequently highlighted a relationship between the effect of pollution from land application of wastewater (Ait Boughrous et al, 2007;Capasso, R, 1995) or the infiltration of leachate (El Adnani et al, 2006) and the sensitivity of the subterranean fauna.…”
Section: Biotic Communities Of the Groundwatersupporting
confidence: 59%
“…This relationship between water quality and richness of stygofauna has already been shown in the case of organic (Ait Boughrous et al, 2007) or inorganic e.g. (El Adnani et al, 2006;El Adnani et al, 2007) pollution. These studies have frequently highlighted a relationship between the effect of pollution from land application of wastewater (Ait Boughrous et al, 2007;Capasso, R, 1995) or the infiltration of leachate (El Adnani et al, 2006) and the sensitivity of the subterranean fauna.…”
Section: Biotic Communities Of the Groundwatersupporting
confidence: 59%
“…Hyporheic animals seem to be less sensitive than their epigean relatives, at least for groups such as typical hyporheic isopods and amphipods (Plénet & Gibert, 1994;Plénet, 1995;Plénet et al, 1996;Plénet, 1999;Williams & Fulthorpe, 2003). However, more recently, El Adnani et al (2007) found that hyporheic fauna may show both qualitative and quantitative changes downstream from metal sulfide tailings containing Pb, Zn and Cu (see also Pyle & Mirza, 2007).…”
Section: Introductionmentioning
confidence: 92%
“…More detailed evaluation of the reviewed studies revealed that 70% of studies in Africa concentrated on the description of newly discovered groundwater fauna (Figure 7a). Nevertheless, more than a dozen of studies in Algeria and Morocco conducted eco‐toxicological investigations, revealing that faunal richness in some urban and mining areas is linked with groundwater quality and stygofauna abundance decreases with pollution (Aidaoui, 2019; Boughrous, 2007; Boughrous et al, 2007; Boulaassafer et al, 2021; Boulal et al, 2017; Boutin et al, 1995; Boutin & Idbennacer, 1989; El Adnani et al, 2006, 2007; el Moustaine et al, 2013, 2014; Hallam et al, 2008; Hichem et al, 2019; Laid & Zouheir, 2018; Merzoug et al, 2011, 2014; Ramzi et al, 2020) with authors proposing the use of stygofauna as bioindicators of water quality (Merzoug et al, 2011, 2014). Boulaassafer et al (2021) study on evolutionary processes considerably expanded the knowledge of diversity and geographic range of a freshwater snail genus, and information on endemism and biogeographical distribution of stygobiotic crustacean species of Africa and Madagascar has been recorded (Tuekam Kayo et al, 2012).…”
Section: Global Groundwater Fauna Researchmentioning
confidence: 99%